Experimentally validated numerical models to assess tsunami hydrodynamic force on an elevated structure - Reis, Cláudia (2021)
Recently, the North American and Japanese authorities began combining the tsunami forces with other loads in their structural design guidelines. Nonetheless, due to the infrequent nature of tsunamis, the provisions may benefit from complementary insights on the qualitative and quantitative characterization of the extreme phenomena and their interaction with coastal structures. The goal of this paper is to explore reliable and relatively accessible computational techniques to determine pressures and forces due to tsunami-like waves on elevated structures. Hydrodynamic flow quantities are simulated for the tsunami-like waves using an Eulerian scheme (Shallow Water equations solved by the Finite Volume method), a Lagrangian scheme (Navier–Stokes equations solved by the Smoothed Particle Hydrodynamics method), and a coupled Eulerian Lagrangian modeling approach. The numerical solutions are validated against experimental data acquired from an experimental campaign performed at the large wave flume of the Hinsdale Wave Research Laboratory, Oregon State University. The correlations between the experimental data and the numerical solutions highlight the advantages and disadvantages of the simulation techniques used, contributing to increase the confidence levels in their use in determining tsunami forces for use in structural assessments and design.